Pre-Service Physics Teacher from Islamic Education Campus Vs. Non-Islamic Education Campus: Which One is more Scientifically Literate? - Masykur, Ruhban; Irwandani, Irwandani; Sari, Putri Mardiana (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study is intended to examine the level of scientific literacy of pre-service physics teachers in Islamic and non-Islamic educational institutions. The research method used document review studies, tests, and observations. The sample selected was 70 pre-service physics teachers consisting of 35 pre-service physics teachers from an Islamic education university and 35 from a non-Islamic educational university. The results of the test show that pre-service physics teachers in an Islamic educational institution have a lower average score than pre-service teachers studying in a non-Islamic educational institution. Through document review and observation, several factors causing the low scientific literacy ability of pre-service physics teachers in Islamic educational institutions were revealed, including the proportion of credits for science courses, supporting facilities and infrastructure, and the quality of teaching staff. This finding is expected to be an evaluation material for policy makers, especially in Islamic educational institutions to make improvements in a structured and systematic way.